Speed and Power Consumption Comparison between DES and AES Algorithm in Arduino - Sukiatmodjo, Arcelina; Setianto, YB Dwi (Universitas Negeri Semarang, 2019)
Telemedicine is commonly used to check or diagnose patients from a long distance. Its application is often combined with sensors as needed, but for delivery, a cryptography algorithm is needed so the data sent safely, illegible, and can not be changed by unauthorized people. Besides that, the algorithm must be light, fast and use less power. In this study, a comparison of the Data Encryption Standard (DES) and Advanced Encryption Standard (AES) algorithms will be implemented in the encryption module. Data from the sensor encrypted and sent to the server. The time and power consumption by DES will be compared with AES. From this research, we can conclude that the encryption time of AES is faster than DES. The average difference speed is 33413 microseconds. Then the power consumption by AES and DES does not have any significant difference, and the addition of sensors causes additional power as well.